2006
DOI: 10.1158/0008-5472.can-05-2183
|View full text |Cite
|
Sign up to set email alerts
|

hTERT-Immortalized Prostate Epithelial and Stromal-Derived Cells: an Authentic In vitro Model for Differentiation and Carcinogenesis

Abstract: Prostate cancer is the most commonly diagnosed type of cancer in men, and there is no available cure for patients with advanced disease. In vitro model systems are urgently required to permit the study of human prostate cell differentiation and malignant transformation. Unfortunately, human prostate cells are particularly difficult to convert into continuously growing cultures. We report here the successful immortalization without viral oncogenes of prostate epithelial cells and, for the first time, prostate s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(121 citation statements)
references
References 45 publications
(63 reference statements)
6
112
0
Order By: Relevance
“…As shown in this study and reported elsewhere [24], urothelial cells, in common with prostate and small airway epithelial cells [29,30], were immortalised by hTERT over-expression alone. Prior to immortalisation, HU-hTERT populations displayed a lag-phase (p11-p13) characterised by reduced growth rates, without senescence or apoptosis.…”
Section: Discussionsupporting
confidence: 87%
“…As shown in this study and reported elsewhere [24], urothelial cells, in common with prostate and small airway epithelial cells [29,30], were immortalised by hTERT over-expression alone. Prior to immortalisation, HU-hTERT populations displayed a lag-phase (p11-p13) characterised by reduced growth rates, without senescence or apoptosis.…”
Section: Discussionsupporting
confidence: 87%
“…All cells were originally obtained from the American Type Culture Collection and cultured in conditions as recommended by the supplier. The hTERT immortalized fibroblast (Pf179T), epithelial (Ep156T), and smooth muscle (Pm151T) cell lines were provided by V. Rotter (Weizmann Institute of Science, Israel) and cultured in conditions as recommended (19). The human primary (nonimmortalized) prostate fibroblast cells isolated from normal (Pt-N) or cancerous (Pt-C) tissues of prostate cancer patients were kind gifts of L. Chung (Emory University) and were cultured as described previously (39).…”
Section: Methodsmentioning
confidence: 99%
“…These methods were chosen because none of the commercially available polyclonal antibodies (2G8 from Abnova, N-19 from Santa Cruz, and ab13291 from Abcam) proved to be effective at detecting Xpr1 expression by Western blotting and/or IHC (data not show). We used a series of telomeraseimmortalized primary cell lines of the epithelial (Ep156T), smooth muscle (Pm151T), and fibroblast (Pf179T) origins that were previously derived from healthy human prostate glands (19). In addition, we also used nonimmortalized fibroblast cell lines, Pt-N and Pt-C, which were derived from benign and malignant prostate tissues, respectively (39), and the established primary prostatic epithelial PrEC cells (Lonza).…”
Section: Xpr1 As a Receptor For Xmrv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…To be able to evaluate the authentic role of p53 in prostate carcinogenesis, we assessed the effect of p53 mutation in EP156T-immortalized prostate epithelial cells. 9 Using this immortalized model, we could manipulate the cells in a controlled way and investigate individual lines with specific genetic alterations. The proliferative behavior of immortalized cells expressing either wt, inactivated or mutated p53 was analyzed, and genomic profiling was performed.…”
mentioning
confidence: 99%